Preparation of Transition Metals Doped SrSnO3 - Dohnalová, Žaneta; Šnajdarová, Martina (Technická univerzita v Košiciach, 2019)
Present work deals with the synthesis and evaluation of physical and chemical properties of SrSn1-xAxO3 perovskite pigments, where A represents doping elements - Fe, Mn, V. These materials were prepared by modified solid state synthesis at high temperature. The main attention was focused to observing the colour properties of the prepared materials and their sun light resistance. Also thermal stability, particle morphology and granulometric composition of the pigments were analysed.
Příprava SrSnO3 dopovaného přechodnými kovy
Keywords: Perovskite; Ceramic pigments; Solid state reaction; perovskit; keramické pigmenty; reakce v pevné fázi